Komunikasi Storytelling Konten Safari Pangus sebagai Pendekatan Soft Selling di Instagram - Putri, Ni Made Amelia Prasetya; Intentilia, Anak Agung Mia (Jurnal Dinamika Ilmu Komunikasi, 2025)
The rapid development of information technology and social media has reshaped how communication and marketing strategies are carried out, including within the scope of micro, small, and medium enterprises (MSMEs). This research examines the use of storytelling communication as a soft selling approach by Safari Pangus, a Balinese traditional clothing MSME, through Instagram. The study applied a descriptive qualitative method with data triangulation, conducted through in-depth interviews, observation, and documentation. Data were analyzed using the AISAS model (Attention, Interest, Search, Action, Share) to understand audience engagement with the content. The findings highlight that storytelling emphasizing customer experiences, production processes, and cultural values—supported by behind-the-scenes content—effectively grabs attention, sparks interest, encourages information-seeking, and drives audience actions. This communication strategy fosters emotional bonds, builds credibility, and enhances brand image without heavy reliance on direct promotion. Consistent yet adaptive content management that integrates videos, photos, and educational material creates authentic and meaningful engagement. Overall, the study shows that storytelling communication functions as a powerful marketing tool to strengthen engagement, raise brand awareness, and build customer loyalty, while also offering a practical reference for other MSMEs to optimize social media use sustainably..